Effectiveness, accountability and understanding board characteristics of non-profit organisations in Malaysia / Norliza Omar … [et al.] - Omar, Norliza; Arshad, Roshayani; Ab Samad, Nur Hayati; Ismail, Rina Fadhilah (Universiti Teknologi MARA Cawangan Selangor, 2016)
Non-profit organisations (NPOs) exist to fulfil the needs of societies that cannot be reached by the government and profit centres. Their ultimate goal is to create social values by solving social problems. In order to fulfil this social mission, it is vital for the NPOs to be effective. NPOs are associated with effective Board of Directors because they are the backbone for organisational success. Of late, there are growing media reports on mismanagement and diversion of NPOs funds. Despite having Board of Directors as trustees in NPOs, mismanagement is still on the rise. Previous findings suggest that NPOs’ board characteristics can be divided into two groups - (1) board characteristics that enhance NPOs’ effectiveness and (2) board characteristics that reduce NPOs’ effectiveness. Hence, this study aims to examine selected board characteristics of Malaysian NPOs. The selected board characteristics are board size, board engagement, board efficiency, board commitment, board with political connection and board professionalism. Using content analysis of NPOs registered under the Companies Commission of Malaysia (CCM), this study finds that, in general, the number of members on the board is seven. Board efficiency and engagement indicate that less than 50% of the members are committed in generating funds for the NPOs. However, results on board commitment indicate that board members are committed in managing their organisations efficiently. In relation to politically affiliated board members and professional affiliation, the results are 44% and 14% respectively. In summary, the findings provide insights on the characteristics of Malaysian NPOs’ board members in. It also provides a basis for future research in examining the influence of board characteristics on effectiveness as well as other areas of concern in NPOs.